Thriving At Work : An Integrative Systematic Literature Review Across Sectors and Countries - Eliyana Eliyana (International Journal of Multidisciplinary Sciences and Arts, 2025)
Thriving at work has emerged as a central construct in contemporary organizational behavior research, particularly in response to post pandemic transformations in work design, technology use, and employee well-being. This integrative systematic literature review synthesizes evidence from 50 Scopus indexed journal articles published between 2020 and 2025, following the PRISMA protocol to ensure transparency and methodological rigor. The review maps the theoretical foundations, research designs, contextual settings, and key empirical findings related to thriving at work. The synthesis reveals that thriving is predominantly grounded in Conservation of Resources Theory, Self Determination Theory, the Job Demands Resources model, and the Socially Embedded Model of Thriving. Empirical findings consistently identify supportive leadership, job resources, and individual psychological capabilities as dominant antecedents, while thriving robustly predicts employee performance, innovative behavior, work engagement, well-being, and reduced turnover intentions. Despite this progress, the literature remains methodologically homogeneous, relying heavily on cross sectional quantitative designs and self reported data, with limited longitudinal, multilevel, and cross cultural investigations. This review highlights notable geographic concentration in Asia, particularly within high pressure service sectors, underscoring the need for broader contextual validation. In response, the study proposes an integrative research agenda that emphasizes longitudinal designs, hybrid and digital work contexts, and the incorporation of emotional and technological demands. By consolidating fragmented findings, this review contributes to theoretical refinement and offers strategic directions for advancing high impact research on thriving at work.